Tumor-specific mutations in the Merkel cell polyomavirus integrated genome. (January 2009) - Segondy, Michel; Foulongne, Vincent
Evaluation of: Shuda M, Feng H, Kwun HJ et al. : T antigen mutations are a human tumor-specific signature for Merkel cell polyomavirus. Proc. Natl Acad. Sci. USA (2008) (Epub ahead of print). Merkel cell carcinoma is a rare but aggressive skin cancer. A new virus belonging to the Polyomaviridae family and named Merkel cell polyomavirus (MCPyV) has been recently identified within Merkel cell carcinoma tumoral tissue specimens with clonal integration of the viral DNA in the genome of carcinoma cells. It is reported in the paper under evaluation that MCPyV genomes in tumoral tissues harbor mutations leading to truncation of the helicase encoded by the large T antigen open reading frame, whereas episomal viral genomes from non-tumoral tissues do not display these signature mutations within the T-antigen open reading frame. The results indicate that the tumor-associated mutations do not affect the large T antigen binding to the retinoblastoma tumor suppressor protein but prevent viral replication. It is demonstrated that wild-type but not truncated large T-antigen expression activates replication of integrated MCPyV. This paper provides convincing evidence that mutations in the T-antigen gene lead to a loss of replicative capacity of the virus, which would be detrimental for cell survival, and therefore might be essential for tumor development. These results are of major importance to understand the role played by MCPyV in carcinogenesis.